2019
DOI: 10.1029/2019ja026743
|View full text |Cite
|
Sign up to set email alerts
|

Highly Relativistic Electron Flux Enhancement During the Weak Geomagnetic Storm of April–May 2017

Abstract: Key Points:• Long-lasting multi-MeV electron enhancement during a period of a relatively weak geomagnetic storm not recorded in GEO. • Electron seed population was accelerated to relativistic energies by the enhanced chorus waves. • Relativistic electrons were further accelerated up to 10 MeV by inward diffusion Corresponding author: Ch. Katsavrias, ckatsavrias@phys.uoa.grWe report observations of energetic electron flux and Phase Space Density (PSD) to show that a relatively weak magnetic storm with Sym−H min… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 46 publications
4
23
0
Order By: Relevance
“…3 , highlighting enhancements. The multistep formation method for >3 MeV electrons, suggested by several authors 16 , 19 , would appear as the profile shown in Fig. 3 d. However, over a time-span of several days, the profiles for both storms shown in Fig.…”
Section: Resultsmentioning
confidence: 88%
See 4 more Smart Citations
“…3 , highlighting enhancements. The multistep formation method for >3 MeV electrons, suggested by several authors 16 , 19 , would appear as the profile shown in Fig. 3 d. However, over a time-span of several days, the profiles for both storms shown in Fig.…”
Section: Resultsmentioning
confidence: 88%
“…3, highlighting enhancements. The multistep formation method for >3 MeV electrons, suggested by several authors 16,19 , would appear as the profile shown in Fig. 3d.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations